Seasonal Abundance and Host-Feeding Patterns of Anopheline Vectors in Malaria Endemic Area of Iran - Hamidreza Basseri; Ahmad Raeisi; Mansoor Ranjbar Khakha; Abaas Pakarai; Hassanzehi Abdolghafar (Journal of Parasitology Research)
Seasonal abundance and tendency to feed on humans are important parameters to measure for effective control of malaria vectors. The objective of this study was to describe relation between feeding pattern, abundance, and resting behavior of four malaria vectors in southern Iran. This study was conducted in ten indicator villages (based on malaria incidence and entomological indices) in mountainous/hilly and plain regions situated south and southeastern Iran. Mosquito vectors were collected from indoor as well as outdoor shelters and the blood meals were examined by ELISA test. Over all 7654 female Anopheles spp. were captured, the most common species were Anopheles stephensi, An. culicifacies, An. fluviatilis, and An. d'thali. The overall human blood index was 37.50%, 19.83%, 16.4%, and 30.1% for An. fluviatilis, An. stephensi, An. culicifacies, and An. d'thali, respectively. In addition, An. fluviatilis fed on human blood during the entire year but the feeding behavior of An. stephensi and An. culicifacies varied according to seasons. Overall, the abundance of the female mosquito positive to human blood was 4.25% per human shelter versus 17.5% per animal shelter. This result indicates that the vectors had tendency to rest in animal shelters after feeding on human. Therefore, vector control measure should be planned based on such as feeding pattern, abundance, and resting behavior of these vectors in the area.